Duality relations associated with weak g-R-duals. Issue 20 (19th December 2022) - Li, Yun-Zhang; Dong, Jian
Abstract : Recently, duality principles in g -frame theory were studied. This paper addresses a relaxation of g -R-duals. We introduce the notion of weak g -R-dual in g -frame theory setting, and present the link between frame properties of a bounded operator sequence and its weak g -R-duals. Using weak g -R-duals, we characterize g -frames and (unitary) equivalence between g -frames. And using pseudo-inverse operators, we represent the canonical duals of weak g -R-duals. Some examples are also provided.